2019
DOI: 10.1371/journal.pone.0214599
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic differences between oligometastatic and polymetastatic extensive disease-small cell lung cancer

Abstract: Purpose Oligometastasis is a state in which cancer patients have a limited number of metastatic tumors; patients with oligometastases survive longer than those with polymetastases. Extensive disease (ED)-small cell lung cancer (SCLC) is considered a systemic disease and a poor survival. This study investigated whether the concept of oligometastases is prognostic factor also applicable to patients with ED-SCLC. Methods We performed a retrospective study of 141 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…Shirasawa et al . also reported prognostic differences between oligometastatic and polymetastatic ED‐SCLC 9 . A total of 49 of the 141 patients in this study were reported to have oligometastatic ED‐SCLC.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Shirasawa et al . also reported prognostic differences between oligometastatic and polymetastatic ED‐SCLC 9 . A total of 49 of the 141 patients in this study were reported to have oligometastatic ED‐SCLC.…”
Section: Introductionsupporting
confidence: 54%
“…Shirasawa et al . reported a better prognosis for oligometastatic ED‐SCLC than polymetastatic disease 9 . Furthermore, the study suggested that local brain irradiation may benefit patients with oligometastatic ED‐SCLC.…”
Section: Discussionmentioning
confidence: 88%
“…This is related to decreased survival (7). However, as in limited-stage disease, it is reported that better treatment responses and survival can be achieved when detected as oligometastatic disease, even if it is an extensive- stage disease (8). Nevertheless, as in the literature, the majority of our patients consisted of extensivestage and poly-metastatic patients.…”
Section: Discussionmentioning
confidence: 55%
“…Early identification and surgical treatment of low volume “oligometastatic” metastatic disease (<5 discrete lesions throughout body within a single “organ”—eg, purely bony metastases)124445…”
Section: What Can Surgery Offer?mentioning
confidence: 99%